Composite electrode wire for linear cutting of hard alloy material and preparation method of composite electrode wire
By using composite electrode wires, the surface layer of copper -zinc alloy and particles with semiconductor functions can be used to solve the problem of slow cutting speed and poor accuracy of hard alloy materials, and achieve a more efficient cutting process and better surface quality.
Patent Information
- Application Number
- CN202411669445.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
The prior art is slow when cutting cemented carbide materials and difficult to improve processing accuracy and surface quality.
A composite electrode wire, which includes a copper-zinc alloy surface with zinc content with zinc content of 20%-43%and zinc content of 40%-85%. The surface layer distribution has irregular micro-nanohole, and it is micro-nano. The surface of the na Kong and the electrode wire adhes up the particles with semiconductor function.
The line cutting speed of the hard alloy material is significantly improved, the processing accuracy and cutting surface quality are improved, and the contact resistance and discharge delay of the electrode wire are reduced.
Smart Images

Figure CN119368845A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode wires for unidirectional wire-cutting electrospark machining, in particular to a composite electrode wire for wire-cutting cemented carbide materials and a preparation method thereof. Background Art
[0002] In the existing technology, motor molds are widely used in automobile manufacturing, aerospace, metallurgical machinery, household appliances, etc. Motor molds made of cemented carbide materials such as tungsten steel, tungsten titanium cobalt, tungsten tantalum cobalt, etc. have the characteristics of high efficiency, high precision, fast changeover and long life in the process of producing motors.
[0003] However, the cemented carbide materials such as tungsten steel, tungsten titanium cobalt, tungsten tantalum cobalt used to make motor molds have the characteristics of high hardness, corrosion resistance, high temperature resistance and small expansion coefficient. Compared with traditional ordinary mold materials such as SKD11, DC53 and SKH-9, there are certain difficulties in the processing process.
[0004] On the other hand, wire cutting or unidirectional wire EDM is a processing method that uses a continuously moving thin metal wire, namely the electrode wire, as an electrode to perform pulsed spark discharge to erode the metal and cut the workpiece into shape. Wire cutting is also widely used in mold manufacturing, especially in the field of motor mold processing. For example, in the field of motor mold processing, wire cutting can achieve high-precision EDM and perform free-form and free-form wire cutting on cemented carbide materials such as tungsten steel, tungsten titanium cobalt and tungsten tantalum cobalt.
[0005] As a precision machining method, unidirectional wire EDM technology can effectively cut these cemented carbide materials, but the cutting speed is relatively slow. This is because cemented carbide materials have extremely high hardness, requiring EDM to have higher energy and stability to ensure cutting speed and machining quality. In addition, the complex shape of cemented carbide materials and fine machining requirements such as the need for multiple knife repairs are also one of the main reasons for the slow cutting speed.
[0006] Although the existing technology provides equipment and technical support such as anti-electrolysis power supply, optimized discharge parameters, multiple cutting technology and high-precision corner control, the processing of some special materials such as tungsten steel, tungsten titanium cobalt and tungsten tantalum cobalt cemented carbides is still limited by material properties, and the cutting speed, processing accuracy and surface quality need to be further improved.
[0007] For example, the applicant's prior invention patent with application number 202010509917.X and titled "An electrode wire for micro-electro-discharge machining, preparation method and application" (hereinafter referred to as Patent 2), the mixed structure of the amorphous layer of the electrode wire reduces the discharge loss of the electrode wire itself, and in the processing of ordinary mold materials, continuous and stable micro-electro-discharge corrosion can be achieved, ensuring the constant gap between the electrode wire and the micro-tool electrode, and improving the online processing accuracy and surface quality; and the main element of the amorphous surface metal is zinc, which has a good gasification effect, helps to improve the discharge efficiency, and can improve the processing speed of ordinary mold materials. However, in the wire cutting processing of cemented carbide materials, due to the irregular arrangement of atoms in the amorphous layer, remote disorder, and high resistivity, the conductivity of the surface layer of the electrode wire material is relatively poor, which makes it difficult to further improve the wire cutting speed of cemented carbide materials.
[0008] For example, the galvanized wire, gamma wire and high-speed plated wire in the existing electrode wire technology achieve good flushing effect by increasing the zinc content in the surface layer, but the conductive properties of the surface material still cannot meet the requirements of rapid electron migration and discharge, which also makes it difficult to further improve the wire cutting speed of cemented carbide materials.
[0009] For example, the applicant's prior invention patent with application number 202111210891.X and name "An electrode wire for electric spark discharge machining and its preparation method" (referred to as Patent 1 in the following table) has a low thermal conductivity coefficient of the electrode wire surface material. During the processing of ordinary mold materials, the heat generated by the electric spark can be more concentrated on the surface of the electrode wire, and a stronger vaporization pressure is generated when it is vaporized, further improving the flushing effect and increasing the cutting speed. However, since the surface layer of the electrode wire is composed of a mixture material, wire cutting of ordinary mold materials has good technical effects. However, for cemented carbide with relatively poor conductivity, the electrode wire surface is not sensitive enough to the micro-current contact induction when it senses the edge, and the edge contact accuracy is not ideal, which directly affects the processing accuracy and surface quality of the cemented carbide material.
[0010] Another example is the high-speed coated wire that is widely used on the market. Since the coating is generally β phase or β+γ phase, or β'+γ phase or β' phase composition, the coating is thick. When cutting ordinary mold materials online, it is more corrosion-resistant than the galvanized layer, the gasification flushing effect is strong and continuous, and the cutting speed is fast. However, if used in wire cutting of cemented carbide, the thicker coating and deeper cracks will seriously reduce the conductivity of the electrode wire surface, making it impossible for the high-speed coated wire to discharge under the weaker discharge energy of fine finishing, which is prone to short circuit and makes the discharge uniformity worse during fine finishing, thus affecting the processing accuracy and surface quality. Summary of the invention
[0011] A technical problem to be solved by the present invention is to provide a composite electrode wire for wire cutting of cemented carbide materials, which can greatly improve the wire cutting speed and has relatively high processing accuracy, and can significantly improve the surface line marks of the cut workpiece and improve the cutting surface quality.
[0012] A technical solution of the present invention is to provide a composite electrode wire for wire cutting of cemented carbide materials, comprising a brass core material with a zinc content of 20%-43% and a copper-zinc alloy surface layer with a zinc content of 40%-85%; the copper-zinc alloy surface layer is distributed with irregular micro-nano pores, each of which extends to the surface of the electrode wire; particles with semiconductor functions are adhered to the micro-nano pores and the surface of the electrode wire.
[0013] After adopting the above content and structure, the composite electrode wire for wire cutting of cemented carbide materials of the present invention has the following advantages:
[0014] The copper-zinc alloy surface of the composite electrode wire of the present invention is distributed with irregular micro-nano pores, and particles with semiconductor functions are adhered in the micro-nano pores and on the surface of the electrode wire, which can quickly gather charges and build an effective conductive network, greatly improving the conductivity of the surface material of the electrode wire under high temperature conditions. Such particles play a role of mutual connection under the action of a pulse power supply, and generate a large number of small currents to gather, and finally gather together to form a discharge channel, accelerate the electron movement rate, perform pulse spark discharge on the workpiece, generate a high temperature of more than 8000-10000°C, etch metal, cut and shape, and improve the cutting speed of machine tools for preparing tungsten steel, tungsten titanium cobalt and tungsten tantalum cobalt and other hard alloy materials for motor molds degree; the irregular micro-nano holes have different micro-morphology and contact surface area, which can bring in more coolant, further improve the flushing effect, promote the next pulse discharge, and maximize the cutting speed of the machine tool for cemented carbide materials; the impedance of the particles with semiconductor functions in the micro-nano holes and adhered to the surface of the electrode wire is relatively low, so the conductivity is better at high temperature. Under the action of the pulse power supply, the discharge gap between the surface of the electrode wire and the workpiece can be optimized, which plays the role of collecting micro-current to reduce the contact resistance of the electrode wire and accelerate the movement rate of electrons. At the same time, it can also effectively reduce the discharge delay and quickly increase the discharge rate, thereby further improving the cutting speed of the machine tool for cemented carbide materials.
[0015] At the same time, since the conductive performance of the electrode wire surface is greatly improved, when cutting tungsten steel, tungsten titanium cobalt, tungsten tantalum cobalt and other hard alloy materials online, the electrode wire surface of the present invention is sensitive to micro-current contact when sensing edge contact, and the edge contact accuracy is greatly improved, thereby greatly improving the processing accuracy of the hard alloy material.
[0016] In addition, the particles with semiconductor functions also act as a conductive promoter during the cutting discharge process, promoting the conductivity between the discharge active substances in the working fluid, reducing the contact resistance between the electrodes, and improving the discharge uniformity, thereby improving the surface line marks of the cutting workpiece and improving the cutting surface quality of the cemented carbide material.
[0017] In summary, the composite electrode wire for wire cutting of cemented carbide materials of the present invention can greatly improve the wire cutting speed of cemented carbide materials, and has relatively high processing accuracy, and can significantly improve the line marks on the surface of the cut workpiece and significantly improve the quality of the cut surface. Of course, it is not difficult to understand that the composite electrode wire has even better performance in wire cutting of other metal materials.
[0018] Furthermore, the particles with semiconductor function are compound semiconductor materials formed by metal and oxygen. After adopting the above structure, the conductive performance of the electrode wire surface is better, and the wire cutting speed, processing accuracy and cutting surface quality of the composite electrode wire for cemented carbide materials are further improved.
[0019] Furthermore, the particles with semiconductor functions are all irregular in shape, the minimum size of a single particle is 1-4700nm, and the maximum size of a single particle is 10-5000nm. After adopting the above structure, the shape of the particles with semiconductor functions has better adhesion to the micro-nano hole and the electrode wire surface, and the size has better adaptability to the micro-nano hole, so that the conductive performance of the electrode wire surface is better, and the wire cutting speed, processing accuracy and cutting surface quality of the composite electrode wire for cemented carbide materials are further improved.
[0020] Furthermore, the particles having semiconductor function are ZnO, CuO, NiO, Cu 2 O、SnO 2 After using the above specific oxides, the conductive property of the electrode wire surface is better, which further improves the wire cutting speed, processing accuracy and cutting surface quality of the composite electrode wire for cemented carbide materials.
[0021] Furthermore, the radial depth dimension of the micro-nano hole is greater than the circumferential width dimension; or the radial depth dimension of the micro-nano hole is greater than the axial length dimension; or the radial depth dimension of the micro-nano hole is greater than the circumferential width dimension and the axial length dimension; or the radial depth dimension of the micro-nano hole is less than the circumferential width dimension; or the radial depth dimension of the micro-nano hole is less than the axial length dimension; or the radial depth dimension of the micro-nano hole is less than the circumferential width dimension and the axial length dimension. After adopting the above structure, the irregular micro-nano holes are gathered along the circumference and along the length on the surface of the electrode wire, and the distribution of semiconductor functional particles is better, so as to further improve the conductive performance of the electrode wire during wire cutting, and further improve the wire cutting speed, processing accuracy and cutting surface quality of the composite electrode wire for cemented carbide materials.
[0022] Furthermore, the thickness of the copper-zinc alloy surface layer is 2-40 μm; the width dimension of each micro-nano hole on the cross section of the electrode wire is 0.1-60 μm, and the depth dimension is 0.2-45 μm; the length dimension of each micro-nano hole on the longitudinal section of the electrode wire is 0.1-40 μm, and the depth dimension is 0.2-45 μm. After adopting the above parameters, the micro-nano holes on the surface of the electrode wire are further improved along the circumference and along the length. The distribution of semiconductor functional particles is further improved, the conductive performance of the electrode wire during wire cutting is further enhanced, and the wire cutting speed, processing accuracy and cutting surface quality of the composite electrode wire for cemented carbide materials are further improved.
[0023] Furthermore, a plurality of micro-nano holes are arranged along the circumference of the electrode wire and along the length of the electrode wire; the particles with semiconductor functions adhered to the micro-nano holes and the surface of the electrode wire are each a plurality of particles. With the above structure, the distribution of the micro-nano holes with semiconductor functions gathered along the circumference and along the length of the electrode wire surface is further improved, the conductive performance of the electrode wire during wire cutting is further enhanced, and the wire cutting speed, processing accuracy and cutting surface quality of the composite electrode wire for cemented carbide materials are further improved.
[0024] Another technical problem to be solved by the present invention is to provide a method for preparing a composite electrode wire for wire cutting of cemented carbide materials, which can prepare a composite electrode wire for wire cutting of cemented carbide materials with fast wire cutting speed, high processing accuracy and good cutting surface quality.
[0025] Another technical solution of the present invention is to provide a method for preparing a composite electrode wire for wire cutting of cemented carbide materials, comprising the following preparation steps:
[0026] 1) Prepare a brass core material with a diameter of 0.7-1.5 mm and a zinc content in the range of 20% to 43%;
[0027] 2) electroplating a zinc-based surface layer on the surface of the brass core material obtained in step 1) at a plating speed of 300-800 m / min, a current of 500-2000 A, a voltage of 5-20 V, and a surface layer thickness of 1-30 μm;
[0028] 3) The wire blank obtained after electroplating is stretched for the first time through a wire drawing die to a diameter of 0.5-1.0 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material, and a dense wire blank having a zinc-based composite layer obtained by the first stretching is obtained;
[0029] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 150-300° C. for a time of 0.5 h to 20 h, and then cooled to below 100° C. and taken out of the furnace to obtain a heat-treated wire blank having a copper-zinc alloy surface layer with a gamma phase structure;
[0030] 5) The heat-treated wire blank is subjected to a second stretching through a wire drawing die to obtain a semi-finished wire blank including a brass core material and a copper-zinc alloy surface layer with micro-nano pores, wherein the diameter of the semi-finished wire blank is 0.35-0.85 mm;
[0031] 6) The semi-finished wire blank obtained by the second stretching is heat treated in an air atmosphere in a furnace at a temperature of 300-500° C. for a time of 2h-30h, and is taken out of the furnace after cooling to below 150° C., to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores and the surface of the electrode wire, wherein the semiconductor material comprises at least zinc oxide, and the zinc content of the surface layer of the copper-zinc alloy is 40%-85% after heat treatment;
[0032] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 500-2000 m / min, and stress relief annealing is performed to obtain a finished electrode wire with a diameter of 0.15-0.30 mm.
[0033] After adopting the above preparation steps, a method for preparing a composite electrode wire for wire cutting of cemented carbide materials has the following advantages:
[0034] The preparation method of the present invention grasps two key preparation process steps: one is to electrodeposit a zinc-based composite layer on the surface of the brass core material; the other is to adhere particles with semiconductor functions in the micro-nano pores and on the surface of the electrode wire, such as the zinc oxide particles and copper oxide particles described below. And through the heat treatment process, the trace elements on the surface diffuse with each other, transfer from the high concentration area to the low concentration area, and distribute more evenly. The preparation method of the present invention can prepare a composite electrode wire for wire cutting of cemented carbide materials with fast wire cutting speed, high processing accuracy and good cutting surface quality.
[0035] Furthermore, in the electrolysis process of step 2), 1-30 kg of 0# zinc block is added per ton of electrodeposition bath liquid, and the zinc content is not less than 99.995%. The brass core material is used as the cathode and the zinc block is used as the anode. After power is turned on, the zinc ions on the zinc block lose electrons under the action of the current and dissolve into the electrolyte to form zinc ions. These zinc ions move to the surface of the brass core material under the action of the electric field, and obtain electrons on the surface of the brass core material, and are reduced to metallic zinc, thereby forming a zinc coating on the surface of the brass core material. After adopting the above preparation process steps, the process is simple and reliable, and a stable and reliable zinc coating is formed on the surface of the brass core material, laying a good coating foundation for the next step of preparing a high-quality copper-zinc alloy surface.
[0036] Furthermore, in step 2), one or two of the trace elements Ni and Sn are added to the electroplating bath, specifically nickel sulfate and / or tin sulfate are added, and the concentration of each added trace element is 1-100 g / L, so that the zinc-based surface layer also contains trace elements Ni and / or Sn to form a zinc-based composite surface layer; the semiconductor material described in step 6) also includes copper oxide, or / and cuprous oxide, or / and nickel oxide, or / and tin oxide. After adopting the above preparation steps, the copper-zinc alloy surface layer adsorbs more types of trace elements, so as to further improve the conductive performance of the electrode wire during wire cutting, and further improve the wire cutting speed, processing accuracy and cutting surface quality of the composite electrode wire for cemented carbide materials.
[0037] Further, in step 6), the chemical reaction process is as follows: 2Zn+O 2 →2ZnO, or / and 2Cu+O 2 →2CuO, or / and 4Cu+O 2 →2Cu 2 O, or / and 2Ni+O 2 →2NiO, or / and Sn+O 2 →SnO 2 .
[0038] After adopting the above preparation process steps, zinc oxide is a wide bandgap semiconductor with wide bandgap, high saturated electron drift velocity and high electron mobility. Therefore, the energy difference between the lower energy level of the conduction band and the highest energy level of the valence band of zinc oxide is very small, and the energy of its electron transition is very close, which makes the electrode wire of the present invention have a faster response speed and higher working efficiency under the condition of high-temperature discharge of electric spark. In the crystal structure of copper oxide, there is an ionic bond between Cu atoms and O atoms. In copper oxide, the Cu atom loses an electron and becomes Cu 2+ ions, while the O atom gains an electron and becomes O 2- Ions. There are vacant oxygen ions in copper oxide, and these vacancies attract free electrons, thus forming hole-type semiconductors in copper oxide. Therefore, the conductivity of copper oxide is related to temperature, and its conductivity becomes better as the temperature rises. In addition, copper oxide also plays a role in improving the reversible capacity, cycle number and charge and discharge stability of the electrode wire during the discharge process. Therefore, zinc oxide, copper oxide, cuprous oxide, nickel oxide and tin oxide all quickly generate and increase a large number of electron-hole pairs as the temperature rises, thereby reducing the resistivity of the electrode wire and significantly improving the conductivity of the product, thereby greatly improving the transmission speed of electrons, having excellent discharge performance and thermal stability, so that the prepared composite electrode wire is used for wire cutting of cemented carbide materials, and has fast wire cutting speed, high processing accuracy and good cutting surface quality.
[0039] Furthermore, the tensile strength of the obtained electrode wire product is 750-1100 MPa, and the conductivity is 19%-28% IACS. After the prepared composite electrode wire has the above properties, the technical effects of fast wire cutting speed, high processing accuracy and good cutting surface quality are further guaranteed. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The cross-sectional enlarged structural diagram of the composite electrode wire of the present invention (particles with semiconductor function are adhered to the surface of the electrode wire) Figure 1 and Figure 2 are not shown).
[0041] Figure 2 It is a schematic diagram of an enlarged longitudinal section of the composite electrode wire of the present invention.
[0042] As shown in the figure:
[0043] 1. Brass core material, 2. Copper-zinc alloy surface layer, 3. Micro-nano pores, 4. Particles with semiconductor functions. DETAILED DESCRIPTION
[0044] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these specific embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each specific embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0045] like Figure 1 and Figure 2 shown.
[0046] The present invention discloses a composite electrode wire for wire cutting of cemented carbide materials, comprising a brass core material 1 with a zinc content of 20%-43% and a copper-zinc alloy surface layer 2 with a zinc content of 40%-85%. The copper-zinc alloy surface layer 2 is distributed with irregular micro-nano pores 3, each of which extends to the surface of the electrode wire. Particles 4 with semiconductor functions are adhered in the micro-nano pores 3 and on the surface of the electrode wire.
[0047] The semiconductor particles are compound semiconductor materials 4 formed of metal and oxygen. The semiconductor particles 4 are all irregular in shape, with the smallest size of a single particle being 1-4700nm and the largest size of a single particle being 10-5000nm. It is not difficult to understand that 4700nm is 4.7μm, which is 4.7 kilonanometers or 4.7 micrometers in words; and 5000nm is 5μm, which is 5 kilonanometers or 5 micrometers in words.
[0048] Because the composite electrode wire of the present invention includes zinc and copper, the particles 4 having semiconductor function include at least ZnO, i.e. zinc oxide, because zinc is easier to oxidize than copper, such as being able to oxidize at a slightly lower temperature and in a slightly shorter time, so zinc oxide is definitely present. It may also include CuO, i.e. copper oxide, Cu 2 O is cuprous oxide. It is not difficult to understand that when copper is less and oxygen is more, cupric oxide is generated, and when copper is more and oxygen is less, cuprous oxide is generated. In step 2), if Ni is added, NiO, that is, nickel oxide, is included. If Sn is added, SnO is included. 2 That is tin oxide.
[0049] The radial depth dimension of the micro-nanopore 3 is greater than the circumferential width dimension; or the radial depth dimension of the micro-nanopore 3 is greater than the axial length dimension; or the radial depth dimension of the micro-nanopore 3 is greater than the circumferential width dimension and the axial length dimension; or the radial depth dimension of the micro-nanopore 3 is smaller than the circumferential width dimension; or the radial depth dimension of the micro-nanopore 3 is smaller than the axial length dimension; or the radial depth dimension of the micro-nanopore 3 is smaller than the circumferential width dimension and the axial length dimension. Figure 2 , the radial depth dimension b of the upper micro-nano hole is greater than the axial length dimension a; the length dimension a of the lower micro-nano hole is greater than the radial depth dimension b.
[0050] The thickness of the copper-zinc alloy surface layer of the final product is preferably 2-40μm; the width dimension of each micro-nanopore on the cross section of the electrode wire is preferably 0.1-60μm, and the depth dimension is preferably 0.2-45μm; the length dimension of each micro-nanopore on the longitudinal section of the electrode wire is preferably 0.1-40μm, and the depth dimension is preferably 0.2-45μm.
[0051] A plurality of micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The micro-nano holes 3 and the particles 4 with semiconductor functions adhered to the surface of the electrode wire are each a plurality of particles.
[0052] It is not difficult to understand that during the stretching process, some of the micro-nanopores 3 coated with the particles 4 with semiconductor functions do not extend to the surface of the electrode wire, but this does not have any side effects, except that the particles 4 with semiconductor functions inside cannot play a conductive role.
[0053] The present invention provides a method for preparing a composite electrode wire for wire cutting of cemented carbide materials, comprising the following preparation steps:
[0054] 1) preparing a brass core material 1 with a diameter of 0.7-1.5 mm and a zinc content in the range of 20% to 43%;
[0055] 2) Electroplating a zinc-based surface layer on the surface of the brass core material obtained in step 1) may add one or two of the trace elements Ni and Sn to the electroplating bath, specifically adding nickel sulfate and / or tin sulfate, and the concentration of each added trace element is 1-100 g / L, so that the zinc-based surface layer also contains trace elements nickel and / or tin to form a zinc-based composite layer. Of course, trace elements may not be added, because the composite electrode wire of the present invention includes copper and zinc, so the particles 4 with semiconductor function include at least ZnO, i.e. zinc oxide, and may also include CuO, i.e. copper oxide and Cu 2 O is cuprous oxide. 1-30 kg of 0# zinc block is added to each ton of electroplating bath liquid, and the zinc content is not less than 99.995%. The brass core material is used as the cathode and the zinc block is used as the anode. After power is applied, the zinc ions on the zinc block lose electrons under the action of the current and dissolve into the electrolyte to form zinc ions. These zinc ions move to the surface of the brass core material under the action of the electric field, and obtain electrons on the surface of the brass core material, and are reduced to metallic zinc, thereby forming a zinc coating on the surface of the brass core material; the electroplating speed is 300-800 m / min, the current is 500-2000 A, the voltage is 5-20 V, and the surface thickness is 3-30 μm;
[0056] 3) The wire blank obtained after electroplating is stretched for the first time through a wire drawing die to a diameter of 0.5-1.0 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense wire blank having a zinc-based composite layer obtained by the first stretching is obtained;
[0057] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 150-300°C for a time of 0.5h-20h, and is cooled to below 100°C and taken out of the furnace to obtain a copper-zinc alloy surface layer with a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the composite surface layer;
[0058] 5) The heat-treated wire blank is subjected to a second stretching through a wire drawing die to obtain a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano pores 3, wherein the diameter of the semi-finished wire blank is 0.35-0.85 mm;
[0059] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace, the heat treatment temperature is 300-500°C, the heat treatment time is 2h-30h, and the wire blank is taken out of the furnace after cooling to below 150°C, and the heat-treated wire blank is obtained, in which particles 4 with semiconductor function formed by metal and oxygen in the air are adhered in the micro-nano pores 3 and on the surface of the electrode wire, and the zinc content of the copper-zinc alloy surface layer 2 is 40%-85%; the chemical reaction process of this step is as follows: 2Zn+O 2 →2ZnO, or / and 2Cu+O 2 →2CuO, or / and 4Cu+O 2→2Cu 2 O, or / and 2Ni+O 2 →2NiO, or / and Sn+O 2 →SnO 2 The semiconductor material includes at least zinc oxide, and also includes copper oxide, or / and cuprous oxide, or / and nickel oxide, or / and tin oxide.
[0060] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 500-2000 m / min, and stress relief annealing is performed to obtain a finished electrode wire with a diameter of 0.15-0.30 mm.
[0061] The obtained electrode wire product has a tensile strength of 750-1100 MPa and a conductivity of 19%-28% IACS.
[0062] It is not difficult to understand that in the preparation process, step 2) a zinc-based composite layer is electroplated on the surface of the brass core material 1, and the coating thickness is 1-30μm, and the subsequent process undergoes two heat treatments. The first heat treatment temperature is 150-300℃, and the heat treatment time is 0.5h-20h. Not only is a composite surface layer containing a gamma phase structure and more uniform trace elements in the composite surface layer obtained, but the chemical components of the core material and the coating diffuse with each other to form a new surface layer with a thickness of 2-50μm. The second heat treatment temperature is 300-500°C, and the heat treatment time is 2h-30h. Not only is a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nanopores 3 and the surface of the electrode wire, but the chemical composition of the two is also changed. The second heat treatment core material and surface layer not only further diffuse, but also transforms the original composite surface layer containing gamma phase structure into a different phase structure to form a copper-zinc alloy surface layer 2 with a zinc content of 40%-85%. More importantly, some surface metal elements such as one or several trace elements of Zn, Cu, Ni and Sn, and oxygen in the air form compound semiconductor materials, namely particles 4 with semiconductor functions, which adhere to the micro-nanopores 3 and the surface of the electrode wire, so the thickness of the copper-zinc alloy surface layer 2 of the electrode wire becomes thinner, such as the thickness of the copper-zinc alloy surface layer 2 is 2-40μm.
[0063] Since the copper-zinc alloy surface layer 2 is hard and brittle after two heat treatments in the subsequent process, the surface layer breaks after stretching to form micro-nanopores 2, and the surface thickness is basically maintained at 2-40μm. The brass core material 1 has good plasticity and toughness. After two subsequent stretchings, the wire diameter gradually decreases, and finally a finished electrode wire with a diameter of 0.15-0.30mm is obtained.
[0064] It is not difficult to understand that during the preparation process of the composite electrode wire, such as electroplating, stretching and heat treatment, not all micro-nanopores 2 are necessarily filled with particles 4 with semiconductor functions, nor is the surface of the electrode wire necessarily evenly and continuously covered with particles 4 with semiconductor functions, but this will not affect the technical effects described in the present invention.
[0065] It is not difficult to understand that a single can also be understood as each. The zinc coating is also called a zinc coating. The copper-zinc alloy surface layer 2 can also be called a zinc-copper alloy surface layer. KG means kilogram. The micro-nano hole 3 is a blind hole, which can also be called a micro-nano pit or crack. The micro-nano hole 3 can penetrate or not penetrate the copper-zinc alloy surface layer, such as Figure 1 As shown in FIG. 1 , five micro-nanopores 3 penetrate the copper-zinc alloy surface layer 2 on the cross section, while the remaining micro-nanopores 3 do not penetrate the copper-zinc alloy surface layer 2. Figure 2 As shown, there are two micro-nano holes 3 on the longitudinal section that penetrate the copper-zinc alloy surface layer 2. Electroplating is also called electrodeposition. The edge contact in wire-cut processing refers to the reference positioning when the machine is turned on, determining the precise starting point of cutting, and ensuring the precise alignment of the cut workpiece with the reference position to improve the processing accuracy. Inductive edge contact refers to the use of micro-current voltage to slowly move the machine head when the machine is turned on, so that the electrode wire slowly approaches the workpiece to obtain the corresponding edge contact accuracy. The edge contact accuracy will directly affect the processing accuracy of the wire-cut. The edge contact accuracy within 0.001-0.002mm is high-precision positioning, within 0.003-0.005mm to meet the basic positioning accuracy, and above 0.010mm is the rough processing positioning accuracy. The edge contact accuracy of the present invention is within the high-precision positioning range described above. The composite surface trace elements described in step 4) above are more uniform, which can be understood as follows: through the heat treatment process, the surface trace elements diffuse with each other and transfer from the high concentration area to the low concentration area, so that they are more evenly distributed.
[0066] The composite electrode wire of the present invention can be used for wire cutting of cemented carbide materials, and can be applied to wire-cutting machine tools produced by Swiss AgieCharmilles, Japanese Mitsubishi, Japanese Sodick, Japanese West and other companies to cut cemented carbide materials such as tungsten steel, tungsten titanium cobalt, tungsten tantalum cobalt and other cemented carbide materials of motor molds.
[0067] The electrode wire for wire-cutting electric discharge machining and the preparation method thereof are further described in detail below in conjunction with the embodiments.
[0068] Example 1
[0069] 1) preparing a brass core material 1 with a diameter of 1.2 mm and a zinc content of 37%;
[0070] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding 20 kg of 0# zinc block per ton of electrodeposition bath liquid, the zinc content is not less than 99.995%, the electroplating speed is 500 m / min, the current is 1500 A, the voltage is 15 V, and the surface layer thickness is 6 μm;
[0071] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.8 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0072] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 210° C. for 8 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0073] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.51 mm;
[0074] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a heat treatment temperature of 450°C for 10 hours, and then cooled to below 150°C and taken out of the furnace to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores 3 and the surface of the electrode wire, and a copper-zinc alloy surface layer 2 having a zinc content of 40%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO and 2Cu+O 2 →2CuO; the semiconductor material is specifically: a plurality of ZnO and CuO particles 4 with semiconductor functions are gathered in the micro-nano hole 3 and adhered to the surface of the electrode wire;
[0075] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 1250 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0076] The tensile strength of the obtained electrode wire product is 870MPa, and the conductivity is 21%IACS. The surface thickness of the final product is 8μm; the width of each micro-nano hole 3 on the cross section of the electrode wire is 0.1-15μm, and the depth is 0.2-11μm; the length of each micro-nano hole 3 on the longitudinal section of the electrode wire is 0.1-12μm, and the depth is 0.2-10μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 10nm, and the maximum size of a single particle is 2000nm.
[0077] Example 2
[0078] 1) preparing a brass core material 1 with a diameter of 1.0 mm and a zinc content of 20%;
[0079] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding trace element nickel such as nickel sulfate to the electroplating bath, wherein the concentration of the trace element nickel is 80 g / L, so that the copper-zinc alloy surface layer contains trace element zinc, trace element copper and trace element nickel to form a zinc-based composite surface layer; adding 15 kg of 0# zinc block per ton of electroplating bath solution, wherein the zinc content is not less than 99.995%, the electroplating speed is 300 m / min, the current is 1200 A, the voltage is 12 V, and the surface layer thickness is 1 μm;
[0080] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.72 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0081] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 180° C. for 6 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0082] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.48 mm;
[0083] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a temperature of 420°C for 10 hours, and then cooled to below 150°C and taken out of the furnace to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores 3 and the surface of the electrode wire, and a copper-zinc alloy surface layer 2 having a zinc content of 45%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO, 2Cu+O 2 →2CuO and 2Ni+O 2 →2NiO; the semiconductor material is specifically: a plurality of ZnO, CuO and NiO particles 4 with semiconductor functions are gathered in the micro-nano hole 3 and adhered to the surface of the electrode wire;
[0084] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 1200 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0085] The tensile strength of the obtained electrode wire product is 750MPa, and the conductivity is 28%IACS. The surface thickness of the final product is 2μm; the width dimension of each micro-nano hole 3 on the cross section of the electrode wire is 0.1-3μm, and the depth dimension is 0.2-3μm; the length dimension of each micro-nano hole 3 on the longitudinal section of the electrode wire is 0.1-2μm, and the depth dimension is 0.2-2.5μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 10nm, and the maximum size of a single particle is 1000nm.
[0086] Example 3
[0087] 1) preparing a brass core material 1 with a diameter of 0.9 mm and a zinc content of 30%;
[0088] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding trace elements such as tin sulfate to the electroplating bath, wherein the concentration of the trace element tin is 60 g / L, so that the copper-zinc alloy surface layer 2 contains trace elements zinc and trace elements tin to form a zinc-based composite surface layer; adding 25 kg of 0# zinc block per ton of electroplating bath, wherein the zinc content is not less than 99.995%, the electroplating speed is 500 m / min, the current is 1800 A, the voltage is 16 V, and the surface thickness is 10 μm;
[0089] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.68 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0090] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 170° C. for 15 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0091] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.45 mm.
[0092] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a temperature of 455°C for 8 hours, and then cooled to below 150°C and taken out of the furnace to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores 3 and the surface of the electrode wire, and the zinc in the copper-zinc alloy surface layer 2 is 50%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO, 2Cu+O 2 →2CuO and Sn+O 2 →SnO 2 The semiconductor material is specifically: a number of ZnO, CuO and SnO particles are aggregated in the micro-nano hole 3 and adhered to the surface of the electrode wire. 2 Particles with semiconductor function 4;
[0093] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 800 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0094] The tensile strength of the obtained electrode wire product is 810MPa, and the conductivity is 26%IACS. The surface thickness of the final product is 14μm; the width of each micro-nano hole 3 on the cross section of the electrode wire is 0.1-15μm, and the depth is 0.2-16μm; the length of each micro-nano hole 3 on the longitudinal section of the electrode wire is 0.1-10μm, and the depth is 0.2-12μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 10nm, and the maximum size of a single particle is 3000nm.
[0095] Example 4
[0096] 1) preparing a brass core material 1 with a diameter of 1.2 mm and a zinc content of 40%;
[0097] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding trace elements Sn such as tin sulfate to the electroplating bath, wherein the concentration of the trace element tin is 80 g / L, so that the copper-zinc alloy surface layer contains trace elements copper, trace elements zinc and trace elements tin to form a zinc-based composite surface layer; adding 25 kg of 0# zinc block per ton of electroplating bath liquid, wherein the zinc content is not less than 99.995%, the electroplating speed is 550 m / min, the current is 1000 A, the voltage is 10 V, and the surface layer thickness is 15 μm;
[0098] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.91 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0099] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 250° C. for 15 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0100] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.65 mm.
[0101] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a temperature of 470°C for 18 hours, and then cooled to below 150°C and taken out of the furnace to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores 3 and the surface of the electrode wire, and a copper-zinc alloy surface layer 2 having a zinc content of 62%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO, 2Cu+O 2 →2CuO and Sn+O 2 →SnO 2 The semiconductor material is specifically: a number of ZnO, CuO and SnO particles 4 with semiconductor functions are aggregated in the micro-nano hole 3 and adhered to the surface of the electrode wire;
[0102] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 1400 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0103] The tensile strength of the obtained electrode wire product is 1030MPa, and the conductivity is 24%IACS. The surface thickness of the final product is 20μm; the width dimension of each micro-nano hole 3 on the cross section of the electrode wire is 0.1-25μm, and the depth dimension is 0.2-45μm; the length dimension of each micro-nano hole 3 on the longitudinal section of the electrode wire is preferably 0.1-20μm, and the depth dimension is preferably 0.2-45μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 10nm, and the maximum size of a single particle is 4000nm.
[0104] Example 5
[0105] 1) preparing a brass core material 1 with a diameter of 1.1 mm and a zinc content of 37%;
[0106] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding 18 kg of 0# zinc block per ton of electrodeposition bath liquid, the zinc content is not less than 99.995%, the electroplating speed is 750 m / min, the current is 900 A, the voltage is 8 V, and the surface layer thickness is 19 μm;
[0107] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.85 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0108] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 230° C. for 14 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0109] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.56 mm;
[0110] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a temperature of 440°C for 10 hours, and then cooled to below 150°C and taken out of the furnace to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores 3 and the surface of the electrode wire, and a copper-zinc alloy surface layer 2 having a zinc content of 47%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO, 2Cu+O 2→2CuO and 4Cu+O 2 →2Cu 2 O; The semiconductor material is specifically: a number of ZnO, CuO and Cu are aggregated in the micro-nano hole 3 and adhered to the surface of the electrode wire. 2 O particles with semiconductor function 4;
[0111] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 1000 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0112] The tensile strength of the obtained electrode wire product is 950MPa, and the conductivity is 23%IACS. The surface thickness of the final product is 27μm; the width of each micro-nano hole 3 on the cross section of the electrode wire is 0.1-40μm, and the depth is 0.2-35μm; the length of each micro-nano hole 3 on the longitudinal section of the electrode wire is 0.1-30μm, and the depth is 0.2-35μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 100nm, and the maximum size of a single particle is 2000nm.
[0113] Example 6
[0114] 1) preparing a brass core material 1 with a diameter of 1.2 mm and a zinc content of 43%;
[0115] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding 28 kg of 0# zinc block per ton of electrodeposition bath liquid, the zinc content is not less than 99.995%, the electroplating speed is 80 m / min, the current is 1200 A, the voltage is 16 V, and the surface layer thickness is 30 μm;
[0116] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.75 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0117] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 175° C. for 12 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0118] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.57 mm.
[0119] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a heat treatment temperature of 450°C for a heat treatment time of 11 hours, and then the wire blank is taken out of the furnace after cooling to below 150°C, and the compound semiconductor material formed by metal and oxygen in the air is adhered to the micro-nano pores 3 and the surface of the electrode wire, and the zinc in the copper-zinc alloy surface layer 2 is 85%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO; the semiconductor material is specifically: a plurality of ZnO particles 4 with semiconductor function are gathered in the micro-nano hole 3 and adhered to the surface of the electrode wire;
[0120] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 1300 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0121] The tensile strength of the obtained electrode wire product is 1100MPa, and the conductivity is 19%IACS. The surface thickness of the final product is 40μm; the width of each micro-nano hole 3 on the cross section of the electrode wire is 0.3-60μm, and the depth is 0.5-30μm; the length of each micro-nano hole 3 on the longitudinal section of the electrode wire is 0.2-40μm, and the depth is 0.6-30μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 50nm, and the maximum size of a single particle is 5000nm.
[0122] Example 7
[0123] 1) preparing a brass core material 1 with a diameter of 1.0 mm and a zinc content of 35%;
[0124] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding trace elements Ni such as nickel sulfate to the electroplating bath, wherein the concentration of the trace element nickel is 60 g / L, so that the copper-zinc alloy surface layer contains trace elements copper, trace elements zinc and trace elements nickel to form a zinc-based composite surface layer; adding 25 kg of 0# zinc block per ton of electroplating bath solution, wherein the zinc content is not less than 99.995%, the electroplating speed is 450 m / min, the current is 1500 A, the voltage is 15 V, and the surface thickness is 12 μm;
[0125] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.81 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0126] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 280° C. for a time of 6 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0127] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.49 mm.
[0128] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a temperature of 425°C for 17 hours, and then taken out of the furnace after cooling to below 150°C, to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores 3 and the surface of the electrode wire, and a copper-zinc alloy surface layer 2 having a zinc content of 59%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO, 2Cu+O 2 →2CuO and 2Ni+O 2 →2NiO; the semiconductor material is specifically: a plurality of ZnO, CuO and NiO particles 4 with semiconductor functions are gathered in the micro-nano hole 3 and adhered to the surface of the electrode wire;
[0129] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 1200 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0130] The tensile strength of the finished electrode wire is 850MPa, and the conductivity is 24%IACS. The surface thickness of the final product is 17μm; the width of each micro-nano hole 3 on the cross section of the electrode wire is 0.1-30μm, and the depth is 0.2-20μm; the length of each micro-nano hole 3 on the longitudinal section of the electrode wire is 0.1-23μm, and the depth is 0.2-19μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 10nm, and the maximum size of a single particle is 5000nm.
[0131] Example 8
[0132] 1) preparing a brass core material 1 with a diameter of 1.2 mm and a zinc content of 40%;
[0133] 2) Electroplating a zinc-based surface layer on the surface of the brass core material 1 obtained in step 1), adding trace elements Ni such as nickel sulfate and trace elements Sn such as tin sulfate to the electroplating bath, wherein the concentration of the trace element nickel is 100 g / L, and the concentration of the trace element tin is 100 g / L, so that the copper-zinc alloy surface layer contains trace elements copper, trace elements zinc, trace elements nickel and trace elements tin to form a zinc-based composite surface layer; adding 25 kg of 0# zinc block per ton of electroplating bath liquid, the zinc content is not less than 99.995%, the electroplating speed is 300 m / min, the current is 1600 A, the voltage is 13 V, and the surface thickness is 23 μm;
[0134] 3) The wire blank obtained after electrodeposition is stretched for the first time through a wire drawing die to a diameter of 0.85 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material 1, and a dense zinc-based composite layer is obtained by the first stretching of the wire blank;
[0135] 4) The wire blank obtained by the first stretching is heat treated at a temperature of 205° C. for 12 hours, and then cooled to below 100° C. to obtain a copper-zinc alloy surface layer 2 having a gamma phase structure and a heat-treated wire blank with more uniform trace elements in the surface layer;
[0136] 5) The heat-treated wire blank is stretched for the second time through a wire drawing die. Since the composite surface layer with the gamma phase structure is relatively hard and brittle, the surface layer is broken after stretching and a number of cracks are formed, that is, a semi-finished wire blank including a brass core material 1 and a copper-zinc alloy surface layer 2 with micro-nano holes 3 is obtained. The several irregular micro-nano holes 3 are arranged along the circumference of the electrode wire and along the length of the electrode wire. The diameter of the semi-finished wire blank is 0.57 mm.
[0137] 6) The semi-finished wire blank obtained by the second stretching is heat treated in the air atmosphere in the furnace at a temperature of 445°C for 20 hours, and then taken out of the furnace after cooling to below 150°C, to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered to the micro-nano pores 3 and the surface of the electrode wire, and a copper-zinc alloy surface layer 2 having a zinc content of 75%. The chemical reaction process of this embodiment is as follows: 2Zn+O 2 →2ZnO, 2Cu+O 2 →2CuO, 2Ni+O 2 →2NiO and Sn+O 2 →SnO 2The semiconductor material is specifically: a number of ZnO, CuO, NiO and SnO are aggregated in the micro-nano hole 3 and adhered to the surface of the electrode wire. 2 Particles with semiconductor function 4;
[0138] 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 1400 m / min, and subjected to stress relief annealing, so that the particles on the surface of the wire blank and between the surface cracks are deformed and redistributed, and a finished electrode wire with a diameter of 0.25 mm is obtained.
[0139] The tensile strength of the obtained electrode wire product is 970MPa, and the conductivity is 23%IACS. The surface thickness of the final product is 35μm; the width of each micro-nano hole 3 on the cross section of the electrode wire is 0.4-45μm, and the depth is 0.2-26μm; the length of each micro-nano hole 3 on the longitudinal section of the electrode wire is 0.3-36μm, and the depth is 0.2-28μm; the particles 4 with semiconductor function are all irregular in shape, the minimum size of a single particle is 30nm, and the maximum size of a single particle is 5000nm.
[0140] Comparative example:
[0141] Comparative Example 1: 0.25 mm brass wire purchased from the market.
[0142] Comparative Example 2: The 0.25 mm galvanized wire purchased from the market has a zinc coating.
[0143] Comparative Example 3: A 0.25 mm gamma electrode wire purchased from the market, the coating of which is a gamma phase. This type of electrode wire is a gamma wire commonly used in the market.
[0144] Comparative Example 4: A 0.25 mm high-speed coated wire purchased from the market, the coating of which is β'+γ phase.
[0145] Comparative Example 5: 0.25mm speed-type electrode wire produced according to Patent 202111210891.X.
[0146] Comparative Example 6: 0.25mm precision electrode wire produced by Patent 202010509917.X.
[0147] The tested wire-cutting machine tool is Sodick ALN400 series wire-cutting machine tool. The processing material is tungsten steel. The processing workpiece thickness is 60mm and the shape is 10*10mm square. It uses 0.25mm electrode wire and performs veneer processing under the conditions of cutting once and repairing twice.
[0148] Compared with the workpieces processed by the electrode wires of Examples 1-8 and the workpieces processed by the electrode wires of Comparative Examples 1-6 in Table 1, the composite electrode wire of the present invention has obvious advantages in cutting speed, processing accuracy and workpiece surface quality (line marks). That is, compared with Comparative Example 1, the cutting speed of the electrode wire of the present invention is increased by 30.58% to 50.41%, and there are no line marks on the surface of the processed workpiece, and the surface quality is more excellent.
[0149] Table 1 is a table of processing test data of the embodiments of the present invention and the comparative examples:
[0150]
[0151] It is not difficult to understand that μm in the table means micrometer. mm in the table means millimeter, which is a unit of length. The smaller the value, the higher the processing accuracy.
[0152] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite electrode wire for wire cutting of cemented carbide materials, comprising a brass core material with a zinc content of 20%-43% and a copper-zinc alloy surface layer with a zinc content of 40%-85%; characterized in that: The copper-zinc alloy surface is distributed with irregular micro-nano pores, each of which extends to the surface of the electrode wire; particles with semiconductor functions are adhered in the micro-nano pores and on the surface of the electrode wire.
2. The composite electrode wire for wire cutting of cemented carbide materials according to claim 1, characterized in that: The particles with semiconductor function are compound semiconductor materials formed by metal and oxygen.
3. The composite electrode wire for wire cutting of cemented carbide materials according to claim 2, characterized in that: The particles with semiconductor functions are all irregular in shape, the minimum size of a single particle is 1-4700nm, and the maximum size of a single particle is 10-5000nm.
4. The composite electrode wire for wire cutting of cemented carbide materials according to claim 2, characterized in that: The particles with semiconductor function are one or more of ZnO, CuO, NiO, Cu2O and SnO2.
5. The composite electrode wire for wire cutting of cemented carbide materials according to claim 1, characterized in that: The radial depth dimension of the micro-nanopore is greater than the circumferential width dimension; or the radial depth dimension of the micro-nanopore is greater than the axial length dimension; or the radial depth dimension of the micro-nanopore is greater than the circumferential width dimension and the axial length dimension; or the radial depth dimension of the micro-nanopore is smaller than the circumferential width dimension; or the radial depth dimension of the micro-nanopore is smaller than the axial length dimension; or the radial depth dimension of the micro-nanopore is smaller than the circumferential width dimension and the axial length dimension.
6. The composite electrode wire for wire cutting of cemented carbide materials according to claim 1, characterized in that: The thickness of the copper-zinc alloy surface layer is 2-40 μm; the width dimension of a single micro-nano hole on the cross section of the electrode wire is 0.1-60 μm, and the depth dimension is 0.2-45 μm; the length dimension of a single micro-nano hole on the longitudinal section of the electrode wire is 0.1-40 μm, and the depth dimension is 0.2-45 μm.
7. The composite electrode wire for wire cutting of cemented carbide materials according to claim 1, characterized in that: A plurality of irregular micro-nano holes are arranged along the circumference of the electrode wire and along the length of the electrode wire; and there are a plurality of particles with semiconductor functions adhered in the micro-nano holes and on the surface of the electrode wire.
8. A method for preparing a composite electrode wire for wire cutting of cemented carbide materials, characterized in that: The process steps include: 1) Prepare a brass core material with a diameter of 0.7-1.5 mm and a zinc content in the range of 20% to 43%; 2) electroplating a zinc-based surface layer on the surface of the brass core material obtained in step 1) at a plating speed of 300-800 m / min, a current of 500-2000 A, a voltage of 5-20 V, and a surface layer thickness of 1-30 μm; 3) The wire blank obtained after electroplating is stretched for the first time through a wire drawing die to a diameter of 0.5-1.0 mm, so that the composite surface layer is evenly distributed on the surface of the brass core material, and a dense wire blank having a zinc-based composite layer obtained by the first stretching is obtained; 4) The wire blank obtained by the first stretching is heat treated at a temperature of 150-300° C. for a time of 0.5 h to 20 h, and then cooled to below 100° C. and taken out of the furnace to obtain a heat-treated wire blank having a copper-zinc alloy surface layer with a gamma phase structure; 5) The heat-treated wire blank is subjected to a second stretching through a wire drawing die to obtain a semi-finished wire blank including a brass core material and a copper-zinc alloy surface layer with micro-nano pores, wherein the diameter of the semi-finished wire blank is 0.35-0.85 mm; 6) The semi-finished wire blank obtained by the second stretching is heat treated in an air atmosphere in a furnace at a temperature of 300-500° C. for a time of 2h-30h, and is taken out of the furnace after cooling to below 150° C., to obtain a wire blank having a compound semiconductor material formed by metal and oxygen in the air adhered in the micro-nano pores and on the surface of the electrode wire, wherein the semiconductor material comprises at least zinc oxide, and the zinc content of the surface layer of the copper-zinc alloy is 40%-85% after heat treatment; 7) The wire blank obtained in step 6) is stretched for the third time at a stretching speed of 500-2000 m / min, and stress relief annealing is performed to obtain a finished electrode wire with a diameter of 0.15-0.30 mm.
9. The preparation method according to claim 8, characterized in that: During the electrolysis process of step 2), 1-30 kg of 0# zinc block is added per ton of electrodeposition bath liquid, and the zinc content is not less than 99.995%. The brass core material serves as the cathode and the zinc block serves as the anode. After power is applied, the zinc ions on the zinc block lose electrons under the action of the current and dissolve into the electrolyte to form zinc ions. These zinc ions move toward the surface of the brass core material under the action of the electric field, and obtain electrons on the surface of the brass core material and are reduced to metallic zinc, thereby forming a zinc coating on the surface of the brass core material.
10. The preparation method according to claim 8, characterized in that: Step 2) adding one or two of the trace elements Ni and Sn to the electroplating bath, specifically adding nickel sulfate and / or tin sulfate, the concentration of the added trace elements is 1-100 g / L each, so that the zinc-based surface layer also contains the trace elements Ni and / or Sn to form a zinc-based composite surface layer; the semiconductor material described in step 6) also includes copper oxide, or / and cuprous oxide, or / and nickel oxide, or / and tin oxide.
11. The preparation method according to claim 10, characterized in that: In step 6), the chemical reaction process is as follows: 2Zn+O2→2ZnO, or / and 2Cu+O2→2CuO, or / and 4Cu+O2→2Cu2O, or / and 2Ni+O2→2NiO, or / and Sn+O2→SnO2.
12. The preparation method according to claim 8, characterized in that: The obtained electrode wire product has a tensile strength of 750-1100 MPa and a conductivity of 19%-28% IACS.
Citation Information
Patent Citations
Efficient electrode wire for precision mould cutting and preparing method of efficient electrode wire
CN103273150A
Electrode wire used for spark cutting of low-speed wire cutting and preparation method of electrode wire
CN105834533A
Wire electrode for electric discharge machining and manufacturing method thereof
CN108856935A
Electrode wire for micro electric spark machining, preparation method and application
CN111590153A
Electrode wire for electrical discharge wire-cutting machining and preparation method electrode wire
CN111843078A